MARGINALIZATION OF CHILDREN WITH SPECIAL EDUCATIONAL REQUIREMENTS (PANGEEA, 2025)
Until the early 1970s, it was believed that the educational needs of these children were so different from those of normal children that they needed special schools with different methods of training and different content. In our country and today many teachers have this opinion. The most important arguments in favor of maintaining the segregationist system are the presence of deficient children in regular classes disrupts classroom activity; in ordinary classes children with disabilities have feelings of inferiority; special schools have specialized staff, who use appropriate educational methods for each category of disability.